An analysis of the Winterveld settlement strategy with special reference to the role of the architects of the National Building Research Institute - Begbie, Ronald (School of Architecture, Planning and Geomatics, 2020)
Architects in South Africa, intentionally or unintentionally, play ~ political role within apartheid ideology each time they hecome involved in housing provision. This thesis will investigate their role within the new housing policies which were heing developed in South Africa in the late 1970's and early 1980's. The specific focus will he an analysis of the work of the Architectural Branch of the National Building Research Institute (N.B.R.I.) who initiated a community participation pro~ess to formulate an upgrading strategy for the Winterveld settlement, 30 km north of Pretoria. An historical perspective will reveal how the plotowner and tenant communities were estahlished in the Winterveld and how conflicts arose hetween these groups, the South African government and the Bophuthatswana government. An investigation of the issues around which these conflicts revolve will reveal why it was that the conflicts could not he resolved. This will, in turn, uncover why it was that in 1980 the architects of the N.B.R.I. initiated a community participation process to formulate an upgrading proposal to deal with the intolerahle living conditions in 1 the settlement. Each stage of the participation process will he discussed and analysed with special emphasis heing placed on understanding how the actions of the architects served various interested parties. It will hecome clear that the architects had no power to intervene as independent arhitrators. Their actions and final proposals were to a large extent hased on their own interests and those of the most powerful actors in the situation. Finally, we shall consider or unintentionally served whether the Architectural Branch intentionally the interests of the apartheid state. Conclusions will he drawn with respect to architects understanding their work from an historical perspective which encompasses a hroad appreciation of economic and political factors.